Impact of Cumulative Fluid Balance During Continuous Renal Replacement Therapy on Mortality in Patients With Septic Acute Kidney Injury: A Retrospective Cohort Study - Lin, Jin; Zhuang, Hai Zhou; Zhi, De Yuan; Qi, Zhili; Bai, Jing; Dong, Lei; Liu, Shuai; Duan, Meili (Frontiers in Medicine, 2021)
Background: The clinicians often use continuous renal replacement therapy (CRRT) for the fluid management of patients with septic acute kidney injury (AKI). However, there is limited knowledge of the effects of changes in fluid balance (FB) on CRRT and its association with outcomes in patients with septic AKI. Objective: This study aimed to determine the association of cumulative FB (CFB) during treatment with 28-day all-cause mortality in the patients with septic AKI who require CRRT. Methods: This retrospective observational study examined patients who received CRRT due to septic AKI in a mixed intensive care unit (ICU) of a tertiary teaching hospital between January 2015 and December 2018. The patients were divided into three groups—negative FB, even FB, and positive FB—based on the CFB during CRRT. The primary outcome was 28-day all-cause mortality. Results: We examined 227 eligible patients and the mean age was 62.4 ± 18.3 years. The even FB group had a significantly lower 28-day mortality (43.0%, p = 0.007) than the positive FB group (72.7%) and the negative FB group (54.8%). The unadjusted and adjusted Cox regression models indicated that the positive FB group had an increased risk for 28-day all-cause mortality relative to the even FB group. A restricted cubic splines model indicated a J-shaped association between the CFB and 28-day all-cause mortality in the unadjusted model. Conclusion: Among the critically ill patients with septic AKI who require CRRT, those with positive FB had a higher mortality rate than those with even FB.